Bridging theory and practice – industry sharing session on soil compaction and consolidation - Keria, Roziah; Ahmad, Azura; Idrus, Juliana; Abdullah, Muhammad Sofian (Unit Penerbitan PKAPP, 2025)
On January 18, 2025, a special industry-sharing session was organized for the Soil Mechanics course, focusing on soil compaction and consolidation. Conducted online, the session was open to all students enrolled in the course. It featured a guest speaker, Ir. Wan Ahmad Syauqi Bin Wan Abdul Rahim, a professional engineer from the Public Works Department (JKR). Ir. Syauqi is a proud alumnus of UiTM Cawangan Pulau Pinang, Permatang Pauh Campus, having graduated in 2018 with a Bachelor of Engineering (Hons.) in Civil (Infrastructure). He achieved his Professional Engineer (Ir.) status in 2023, just five years after graduation, which is a notable accomplishment. He has extensive experience in geotechnical engineering in Malaysia and internationally and has often been invited as a speaker and presenter at various technical seminars and training sessions. During the session, Ir. Syauqi provided students with a clear and insightful experience of the practical application of soil compaction and consolidation in real-world engineering projects. He shared real challenges faced on construction sites and the decision-making processes involved. This helped students connect classroom theories to actual field practices.